2023
DOI: 10.1021/acs.inorgchem.3c01056
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning MOFs with Amino Group for One-Step Ethylene Purification from the C2 Hydrocarbon Mixture

Abstract: Due to the similar kinetic diameters of C2H2, C2H4, and C2H6, one-step purification of C2H4 from a ternary C2H2/C2H4/C2H6 mixture by adsorption separation is still a challenge. Based on a C2H6-trapping platform and crystal engineering strategy, the N atom and amino group were introduced into NTUniv-58 and NTUniv-59, respectively. Gas adsorption testing of NTUniv-58 showed that both the C2H2 and C2H4 uptake capacities and the C2H2/C2H4 separation ability were boosted compared with the original platform. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…For the 1:99 C 2 H 2 /C 2 H 4 mixture, the selectivity at 1 atm and 298 K was 19.8, which was higher than that of NOTT-300 (2.17), Dy-MOF (1.1), dia-[Sc­(Hpzc)­(pzc)] (3.1), ZJNU-119 (3.5), FeMOF-74 (2.08), ZJNU-14 (1.59), NUC-19 (4.0), and Cu­(TIA) (2.09) (Table S1). For the 10:90 C 2 H 6 /C 2 H 4 mixture, the selectivity at 1 bar and 298 K was 1.6, which was close to that of Zn-atz-ipa (1.67) and higher than that of TJT-100(1.2), Azole-Th-1 (1.46), and JNU-2(1.5) …”
mentioning
confidence: 64%
“…For the 1:99 C 2 H 2 /C 2 H 4 mixture, the selectivity at 1 atm and 298 K was 19.8, which was higher than that of NOTT-300 (2.17), Dy-MOF (1.1), dia-[Sc­(Hpzc)­(pzc)] (3.1), ZJNU-119 (3.5), FeMOF-74 (2.08), ZJNU-14 (1.59), NUC-19 (4.0), and Cu­(TIA) (2.09) (Table S1). For the 10:90 C 2 H 6 /C 2 H 4 mixture, the selectivity at 1 bar and 298 K was 1.6, which was close to that of Zn-atz-ipa (1.67) and higher than that of TJT-100(1.2), Azole-Th-1 (1.46), and JNU-2(1.5) …”
mentioning
confidence: 64%
“…S1). For the 1:30 C 2 H 6 /C 2 H 4 mixture, the selectivity at 298 K and 1 atm was 2.85, which exceeded that of TJT-100(1.2), 6a Zn-atz-ipa (1.67), 22 JNU-2(1.5), 23 and Azole-Th-1 (1.46). 6b Additionally, for the 1:30 CO 2 /C 2 H 4 mixture, the selectivity at 298 K and 1 atm was 3.18.…”
mentioning
confidence: 82%
“…For the PCN-306 material studied by Chen and co-workers, the experiments found that V-type carboxylic ligands can improve gas adsorption capacity by grafting polar functional groups. Significantly, the transformation of ligand bodies (benzene ring, triazole, urea group) and the introduction of functional groups (−NO 2 , −NH 2 , −CH 3 , and −F) in isostructural PMOF can effectively regulate the pore environment engineering and achieve efficient gas storage and purification.…”
Section: Introductionmentioning
confidence: 99%